The Traditional Anak Daro Clothes Of Salayo, Solok District West Sumatera:A Semiotic Analysis - Fauzia, Tamara; Aditiawarman, Mac (Fakultas Sastra Universitas Ekasakti, 2025)
The purpose of this study is to reveal the meaning and signs of clothes worn by anak daro and introduce and preserve Minangkabau culture, especially in traditional wedding clothes in Nagari Salayo, Solok District. This research resulted in the meaning of the signs on the clothes and attributes worn by the bride during the wedding party. These meanings are categorized into 3 parts. These meanings are categorized into 3 parts. First, it reflects the state of flora and fauna in the surrounding nature, such as bungo sanggua banana saparak, dukuah rago, dukuah ramo-ramo, tali baju, tabua, galang munggu, galang leaves. Second, the Salayo community does not forget the rules of custom and religion, this can be seen in the attributes of dukuah pinyaram. The symbolic meaning of the marriage symbols as a whole is a form of respect, while the symbolic meaning contained in the traditional clothes of the Salayo children is a form of responsibility and life lived during marriage.The method used in this research is descriptive qualitative research method. The main data collection techniques in qualitative research are observation, in-depth interviews, and supplemented by documentation studies. The data analysis technique is to explain the clothing attributes and interpret each sign on the attributes using the theory proposed by Ferdinand de Saussure, namely Semiotics.